Stability performance analysis of Fe based MOFs for peroxydisulfates activation to effectively degrade ciprofloxacin - Geng, Fang-Lan; Chi, Hai-Yuan; Zhao, Hua-Chao; Wan, Jin-Quan; Sun, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Fe-based metal-organic frameworks (MOFs) show high activity towards the activation of peroxodisulfate (PDS) for the removal of organic micropollutants (OMPs) in wastewater treatment.However, there is a phenomenon of Fe ion dissolution in the Fe-based MOFs' active PDS system, and the reasons and influencing factors that cause Fe ion dissolution are poorly understood. In this study, we synthesized four types of Fe-based MOFs and confirmed their crystal structure through characterization. All types of Fe-based MOFs were found to activate PDS and form sulfate radicals (SO4 −• ), which effectively remove OMPs in wastewater. During the process of Fe-based MOFs activating PDS for CIP removal, activated species, oxidant reagent, and pH negatively impact the stability performance of the MOFs' structure. The coordination bond between Fe atom and O atom can be attacked by water molecules, free radicals, and H + , causing damage to the crystal structure of MOFs. Additionally, Fe(II)-MOFs exhibit the best stability performance, due to the enhanced bond energy of the coordination bond in MOFs by the F ligands. This study summarizes the influencing factors of Fe-based MOFs' damage during PDS activation processes, providing new insights for the future development of Fe-based MOFs.